2007
DOI: 10.1007/s00421-007-0479-7
|View full text |Cite
|
Sign up to set email alerts
|

Four weeks one-leg training and high fat diet does not alter PPARα protein or mRNA expression in human skeletal muscle

Abstract: 4 weeks one leg knee extensor training did not affect PPARalpha protein or mRNA expression. Furthermore, higher fat oxidation during exercise after fat rich diet was not accompanied by an increased PPARalpha protein or mRNA expression after 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
12
0
2
Order By: Relevance
“…This agrees with data in collected in humans, which indicated that PPARα expression does not appear to change with exercise changing in the quadriceps muscle [16]. Interestingly, the loss of PPARα expression in mice resulted in significant reductions in exercise capacity, without significant alterations in metabolic capacity of the muscle, which was predicted to be the result compensatory increase in PPARβ/δ expression [17].…”
Section: Discussionsupporting
confidence: 87%
“…This agrees with data in collected in humans, which indicated that PPARα expression does not appear to change with exercise changing in the quadriceps muscle [16]. Interestingly, the loss of PPARα expression in mice resulted in significant reductions in exercise capacity, without significant alterations in metabolic capacity of the muscle, which was predicted to be the result compensatory increase in PPARβ/δ expression [17].…”
Section: Discussionsupporting
confidence: 87%
“…45 In humans, it was observed that 4 weeks of training was able to improve oxidative capacity even without changes on PPAR-α mRNA or protein expressions on skeletal muscle. 46 However, different isoforms of the PPARα co-activator, PGC-1α, has been described as activated by a single bout of exercise in skeletal muscle. 47 PGC-1α is a regulator of mitochondrial biogenesis in tissues with high-energy demands, such as heart and skeletal muscle.…”
Section: Figurementioning
confidence: 99%
“…Overall, the quality of the manuscripts included in the review was moderate to high (Mean = 11 ± 2 of a possible 16). Participant characteristics (eligibility criteria) were not included in 45% of the studies (n = 14) (Cameron‐Smith et al, ; Arkinstall et al, ; Holloway et al, , ; Helge et al, ; Talanian et al, , ; de Bock et al, ; Tjonna et al, ; Yeo et al, ; Cheng et al, , ; Hulston et al, ; Bradley et al, ), and the exercise stimuli involved in each study was clearly described in all bar one manuscript (Mensink et al, ). All studies investigating acute exercise, bar one (Holloway et al, ), were deemed to use adequate adjustment for confounders, however only 12 (Kiens et al, ; Tunstall et al, ; Cameron‐Smith et al, ; Schenk and Horowitz, ; Burgomaster et al, ; Talanian et al, ; de Bock et al, ; Perry et al, ; Yeo et al, ; Hulston et al, ; van Proeyen et al, ; Jeppesen et al, ) intervention studies were considered to do the same.…”
Section: Resultsmentioning
confidence: 99%
“…The overall quality of the reporting of individual study results, including statistical significance, was poor amongst the manuscripts included in this review. Reporting of estimates of the random variability in the data relating to the main outcome only occurred in nine studies (Kiens et al, ; Mensink et al, ; Arkinstall et al, ; Schenk and Horowitz, ; Helge et al, ; Fu et al, ; Rimbert et al, ; Newsom et al, ; Cheng et al, ), and actual P ‐values were only reported in five manuscripts (Tunstall et al, ; Mensink et al, ; de Bock et al, ; Fu et al, ; Newsom et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation